Ribavirin Treatment for Severe Schizophrenia with Anti-Borna Disease Virus 1 Antibodies 30 Years after Onset - Matsunaga, Hidenori; Fukumori, Akio; Mori, Kohji; Morihara, Takashi; Sato, Shunsuke; Kitauchi, Kyoko; Yanagida, Kanta; Taguchi, Kazumi; Honda, Tomoyuki; Tomonaga, Keizo (Case Reports in Psychiatry, 2023)
Objective. Borna disease virus 1 (BoDV-1) was proven to cause fatal encephalitis in humans in 2018. However, the effects of persistent infections remain unclear. Here, we present the case of a 50-year-old woman with a 30-year history of severe schizophrenia, who was exposed to fleas from stray cats prior to disease onset, suggesting the possibility of zoonosis including BoDV-1 infection. The patient had experienced significant social impairment, thought deterioration, delusions, and hallucinations for more than 20 years. Method. A radioligand assay was used to test the patient for IgG and IgM antibodies against BoDV-1 nucleoprotein (N) and phosphoprotein (P). Based on the protocol for hepatitis C, we treated the patient with 400 mg/day ribavirin, which was later increased to 600 mg/day. Results. The serological examination revealed anti-BoDV-1 N IgG. Although only subtle changes were observed over the 24 weeks of treatment, the family noticed that the patient’s Cotard delusions had disappeared 7 months after completing the treatment, accompanied by some improvements in the relationship with the family. Conclusion. Though definite proof was not obtained, this presumed suppression of BoDV-1 by ribavirin leading to improvements in Cotard syndrome-like symptoms suggests that intractable schizophrenia might be one of the BoDV-1 infection phenotypes. Further studies are needed to clarify the effect of persistent BoDV-1 infections in humans.